2015
DOI: 10.1002/2014pa002681
|View full text |Cite
|
Sign up to set email alerts
|

New insights into productivity and redox‐controlled trace element (Ag, Cd, Re, and Mo) accumulation in a 55 kyr long sediment record from Guaymas Basin, Gulf of California

Abstract: A high-resolution, 55 kyr long record of chalcophile and redox-sensitive trace element accumulation (Ag, Cd, Re, and Mo) from MD02-2515, western Guaymas Basin, is investigated in conjunction with patterns in stratigraphy and productivity. High opal concentrations (~59 wt. %), representing increased diatom production, coincide with laminated sediments and dilute the concentrations of organic carbon (C org ) and metals. A similarity between opal and normalized C org , Ag, and Cd concentrations suggests delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 108 publications
(212 reference statements)
0
14
0
Order By: Relevance
“…The net decline in export production observed in this study was dominated by the decline in tropical and subtropical waters. Many palaeoproductivity studies located outside of the subantarctic zone have found weakened productivity at the LGM (Chang et al, 2014(Chang et al, , 2015Costa et al, 2016;Crusius et al, 2004;Kohfeld et al, 2005;Kohfeld and Chase, 2011;Jaccard et al, 2005;McKay et al, 2015;Ortiz et al, 2004;Riethdorf et al, 2013;Salvatteci et al, 2016;Singh et al, 2011;Thomas et al, 1995). Additionally, an enhanced utilisation of available nutrients in the subantarctic zone would reduce the nutrient content of intermediate waters formed in the Southern Ocean and would thus reduce the delivery of nutrients to lower latitudes (Sarmiento et al, 2004).…”
Section: Reconciling Export Productionmentioning
confidence: 99%
“…The net decline in export production observed in this study was dominated by the decline in tropical and subtropical waters. Many palaeoproductivity studies located outside of the subantarctic zone have found weakened productivity at the LGM (Chang et al, 2014(Chang et al, , 2015Costa et al, 2016;Crusius et al, 2004;Kohfeld et al, 2005;Kohfeld and Chase, 2011;Jaccard et al, 2005;McKay et al, 2015;Ortiz et al, 2004;Riethdorf et al, 2013;Salvatteci et al, 2016;Singh et al, 2011;Thomas et al, 1995). Additionally, an enhanced utilisation of available nutrients in the subantarctic zone would reduce the nutrient content of intermediate waters formed in the Southern Ocean and would thus reduce the delivery of nutrients to lower latitudes (Sarmiento et al, 2004).…”
Section: Reconciling Export Productionmentioning
confidence: 99%
“…(2005) (Barron et al ., 2004; Keigwin & Jones, 1990; Pride et al ., 1999); data from Core MD02‐2515 as in Chang et al . (2015) (Cheshire & Thurow, 2013; Pichevin et al ., 2014), Core JPC20 data ( this study ) show a 3‐point running average. Black arrows show increases/decreases in percentages of biogenic components during stadial events.…”
Section: Resultsmentioning
confidence: 99%
“…8G). In terms of biological productivity, a regional decrease in biogenic silica occurred during H2, H1 and YD events, but increase during B/A, as previously recognised (Barron et al ., 2005, 2014; Chang et al ., 2015; McClymont et al ., 2012; Pichevin et al ., 2014). As a general hypothesis, a change toward warmer sea surface temperatures (SST) can mirror an upwelling reduction, due to the latitudinal displacement of the ITCZ and a weaker subtropical jet that impedes winter to early spring upwelling from developing (Barron et al ., 2014; McClymont et al ., 2012; Oster et al ., 2015; Pichevin et al ., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations